2021
DOI: 10.1002/anie.202101069
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Mesostructured NiO Films with Spin Polarisation

Abstract: Spin polarisation is found in the centrosymmetric nonferromagnetic crystals, chiral mesostructured NiO films (CMNFs), fabricated through the symmetry‐breaking effect of a chiral molecule. Two levels of chirality were identified: primary nanoflakes with atomically twisted crystal lattices and secondary helical stacking of the nanoflakes. Spin polarisation of the CMNFs was confirmed by chirality‐dependent magnetic‐tip conducting atomic force microscopy (mc‐AFM) and magnetic field‐independent magnetic circular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 36 publications
2
61
0
1
Order By: Relevance
“…17 Recent transmission electron microscopy (TEM) studies of similar compounds by Bai et al furthermore indicate that the bulk crystal structure of the investigated nickel and iron oxide films is chirally distorted. 28,29 To confirm that the films investigated in this study are chiral as expected, transmission circular dichroism (CD) spectra were acquired from each sample prior to the photoemission measurements. Figure 2a shows representative CD spectra measured on 40 nm CuO thin films of both L and D chirality.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…17 Recent transmission electron microscopy (TEM) studies of similar compounds by Bai et al furthermore indicate that the bulk crystal structure of the investigated nickel and iron oxide films is chirally distorted. 28,29 To confirm that the films investigated in this study are chiral as expected, transmission circular dichroism (CD) spectra were acquired from each sample prior to the photoemission measurements. Figure 2a shows representative CD spectra measured on 40 nm CuO thin films of both L and D chirality.…”
Section: Resultsmentioning
confidence: 74%
“…Switzer et al also demonstrated that the chiral films can act as enantioselective catalysts . Recent transmission electron microscopy (TEM) studies of similar compounds by Bai et al furthermore indicate that the bulk crystal structure of the investigated nickel and iron oxide films is chirally distorted. , …”
Section: Resultsmentioning
confidence: 98%
“…Multilevel three-dimensional (3D) lms (ZnO, silver, CuO, NiO, and so on), with hierarchical chirality from the atomic to the micron scales, were constructed using a symmetry-breaking agent, and their cooperative assembly effect was studied. [73][74][75][76] Each lm contained three levels of chirality, which were identied with structural characterization: (1) primary distorted nanoakes/ nanoplates with atomic crystal lattices; (2) secondary helical stacking of these nanoakes to form nanoplates; and (3) tertiary micrometer-sized circinate aggregates of the chirally arranged nanoplates. Lattice defects were induced by the chiral center of the amino acid, which ultimately led to a circinate helical conguration.…”
Section: Chiral Nanolmsmentioning
confidence: 99%
“…For example, chiral nematic TiO 2 [6] and SiO 2 [7] films synthesized by cellulose liquid crystal templates, and chiral inorganic photonic crystal films with layer‐by‐layer Langmuir‐Schaefer assembly of achiral inorganic NiMoO 4 nanowires, [8] which displayed different colours under left‐ and right‐handed circularly polarized light filters (L‐ and R‐CPFs). Recently, we synthesized various chiral inorganic films, [4f,i, 9] such as SiO 2 , ZnO, CuO, TiO 2 , NiO, Ag, Au, and SnO 2 films, with multilevel chiral structures and adjustable OAs using chemical growth methods. Regrettably, none of these films exhibits the circularly polarized colour response due to their relatively weak OAs and narrow optical response band.…”
Section: Figurementioning
confidence: 99%